Assessment of Psychiatric Morbidity Among Health Care Workers During COVID-19 Pandemic in A Tertiary Care Hospital in Bangladesh - Ahmmad, Julhash Uddin; Shams, S M Khalid; Hassan, Nazmul; Miah, Md Titu; Islam, Md Azizul; Ahmed, Md Sharif (Journal of Bangladesh College of Physicians and Surgeons, 2023)
Introduction: Assessment of the symptoms of anxiety, depression, stress and feeling of wellbeing among healthcare workers are essential to take necessary steps to treat or prevent any psychiatric morbidity. Objective: The objective of the study was to assess the psychiatric morbidity among the healthcare workers of a tertiary level hospital in Bangladesh. Methods: This was a cross sectional study conducted in Combined Military Hospital, Bogura, Bangladesh from July 2021 to December 2021. For this purpose, 50 health workers fulfilling inclusion and exclusion criteria were taken as sample. They filled up personal & sociodemographic data and the short-form Bangla version of WHO-5, GAD-7, PHQ- 9andPSS-5 scale [1,2,3,4,18]. The results showed that the mean age of the health workers was average 25 years with male predominance (58%). Symptoms of anxiety, depression, stress and wellbeing were found among 20%, 30% ,96% and 96% of health workers respectively. This excess stress and low feeling of wellbeing may be related to extra stressors caused by dread, fear and exceptional longevity of the disease itself and sudden socioeconomic drift down compounded by Covid-19 pandemic effects. Combination of depression, anxiety and stress in different patterns were also higher in them. Conclusions: Incidence of psychiatric illness was high among health care workers during the COVID-19 pandemic. Further larger studies are required to categories these illness and to find out help to overcome. J Bangladesh Coll Phys Surg 2023; 41: 212-218